B‐type natriuretic peptide and heart failure: what can we learn from clinical trials?. (25th August 2015) - Binoun‐A‐Egom, Christian; Andreas, Angelo; Klimas, Jan; Valentova, Vanda; Kruzliak, Peter; Egom, Emmanuel E
Summary The B‐type natriuretic peptide (BNP) may favour natriuresis and diuresis, making it an ideal drug to aid in diuresing a fluid‐overloaded patient with poor or worsening renal function. Several randomized clinical trials have tested the hypothesis that infusions of pharmacological doses of BNP to acute heart failure (HF) patients may enhance decongestion and preserve renal function in this clinical setting. Unfortunately, none of these has resulted in a better outcome. The current challenge for BNP research in acute HF lies in a failure of concept and reluctance to abandon a demonstrably ineffectual research model. Future success will necessitate a detailed understanding of the mechanism of action of BNP as well as a better integration of basic and clinical science.